Observation of the spin-orbit interaction in bremsstrahlung - Tashenov, Stanislav; Bäck, Torbjörn; Barday, Roman; Cederwall, Bo; Enders, Joachim; Khaplanov, Anton; Fritzsche, Yulia; Schässburger, Kai-Uwe; Surzhykov, Andrey; Yerokhin, Vladimir (Physica scripta, 2013)
The effects of the spin-orbit interaction are pronounced for an electron scattered in a Coulomb field of the nucleus. They cause the electron scattering plane to turn or precess as the electron moves. This precession is visible through linear polarization of bremsstrahlung. The first experiment to observe it is described in this contribution.